2016
DOI: 10.1080/2162402x.2015.1093721
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of KIR inhibitory ligands (HLA-I) determines that immunosurveillance of myeloma depends on diverse and strong NK cell licensing

Abstract: L3¡ (20% vs. 83%, p < 0.00001) as well as KIR3DL1 ¡ (23% vs. 82%, p < 0.00001) genotypes had a dramatic negative impact on the 3-y progression-free survival (PFS), particularly in patients with lowtumor burden. Remarkably, myeloma-PCs, compared to K562 and other hematological cancers, showed substantial over-expression of HLA-I ("increasing-self" instead of missing-self), including HLA-C, and mild expression of ligands for NKc activating receptors (aRec) CD112, CD155, ULBP-1 and MICA/B, which apparently render… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 55 publications
(66 reference statements)
2
29
1
Order By: Relevance
“…3A). Lower progression-free rates were observed for both HLA-C*16:01 (8.3%) and Genetic data from bladder cancer, OSC [23], and PCD [24] series coincides with a series used in previous studies aimed at describing the role of NK cell education in tumor immune surveillance. * HLA-I ligands for KIR2DS4 [21].…”
Section: 3supporting
confidence: 78%
See 2 more Smart Citations
“…3A). Lower progression-free rates were observed for both HLA-C*16:01 (8.3%) and Genetic data from bladder cancer, OSC [23], and PCD [24] series coincides with a series used in previous studies aimed at describing the role of NK cell education in tumor immune surveillance. * HLA-I ligands for KIR2DS4 [21].…”
Section: 3supporting
confidence: 78%
“…The 10-yr progression-free rates were 89.5% for CIS + Ta, 82.1% for T1, and 42.9%, 33.3%, and 37.5% for T2/T4 after cystectomy, cystectomy + chemotherapy, and palliative, respectively. Genetic data for BC, OSC, and PCD patients coincide with a series of patients included in previous studies [22,24]. BC patients showed a significantly higher frequency of KIR2DL5 (66.7%, p c = 0.004) than HC (51.5%), OSC (56.7%), and PCD (54.9%) patients.…”
Section: Demographic Clinical and Treatment Detailssupporting
confidence: 77%
See 1 more Smart Citation
“…NKc education is also important in an autologous setting and contributes to immune surveillance against solid tumors (11). This is particularly relevant when transformed cells do not downregulate, but instead upregulate HLA expression, as has been reported in myelomas where the overexpression of HLA-I makes effective cancer immune surveillance highly dependent on multiple and diverse licensing interactions (12).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, these variations are not restricted to activators on NK cells. Some studies had shown that NK cell impairment was associated with upregulated receptors expression such as NKG2A, KIR2DL1/L2/L3 [13][14][15]. In the liver, NK cells enrich remarkably, where the importance of cytotoxicity and antitumor immunomodulation induced by those cells is broadly recognized.…”
mentioning
confidence: 99%